Fishermen's House, Form And Culture At Bangkalan Coastal Area, Madura Island - Sharvina, Ainun; Faqih, Muhammad; Santosa , Happy Ratna; Setijanti , Purwanita; Yusuf , Mimin Aminah (EMARA: Indonesian Journal of Architecture, 2025)
House, form and culture are widely discussed in vernacular architecture, especially in the inland settlement. Indonesia archipelagos have many coastal vernacular settlements and domestic architecture along the island’s coastline. To enrich Indonesia vernacular architecture, exploring fishermen costal settlement is necessary. The characteristic to that of fishermen’s settlement along the coastal area is different to that of Madura inland sedentary agriculture settlement in terms of its architectural form and cultural expression. This research aims to reveal the relation of form and culture of fishermen settlements by conducting descriptive qualitative study. The data collection consists of field observations, sketches and photographs, in-depth interviews and survey questionnaire. The data is analyzed and assessed with the theory of house, form and culture. The result of the study showed that there are several cultural values of inland settlement expressed in the architectural forms in fishermen’s housing of Madura's coastal area.